Dendrobium huoshanense polysaccharide regulates hepatic glucose homeostasis and pancreatic β-cell function in type 2 diabetic mice. (1st May 2019) - Wang, Hong-Yan; Li, Qiang-Ming; Yu, Nian-Jun; Chen, Wei-Dong; Zha, Xue-Qiang; Wu, De-Ling; Pan, Li-Hua; Duan, Jun; Luo, Jian-Ping
Graphical abstract: Highlights: D. huoshanense polysaccharide (GXG) ameliorates hyperglycemia in type 2 diabetic mice. GXG attenuates the loss of pancreatic β-cell mass and function. GXG regulates glucose metabolism via IRS1-PI3K-Akt-FoxO1/GSK-3β signaling pathways. Abstract: In the present study, the hypoglycemic mechanism of a homogeneous Dendrobium huoshanense polysaccharide (GXG) was investigated using type 2 diabetic (T2D) mouse model. With a 5-week oral administration of GXG, the levels of fasting blood glucose, glycosylated serum protein and serum insulin in T2D mice were decreased, and the glucose tolerance and the insulin sensitivity were improved. The histological analysis, the periodic acid-schiff staining and the immunofluorescence staining of insulin, glucagon and apoptosis showed that the hypoglycemic effect of GXG was related to the improvement of pancreatic β-cell quantity and function and the regulation of hepatic glucose metabolism. Western blot analysis indicated that the up-regulated IRS1-PI3K-Akt phosphorylation followed by the down-regulated FoxO1/GSK 3β phosphorylation contributed to the enhanced glycogen synthesis and the decreased gluconeogenesis by GXG, suggesting that the response of insulin-mediated IRS1-PI3K-Akt-FoxO1/GSK 3β signaling to GXG might be the required mechanism for GXG-ameliorated development of type 2 diabetes.